Low Temperature and Short-Term High-CO2 Treatment in Postharvest Storage of Table Grapes at Two Maturity Stages: Effects on Transcriptome Profiling - Rosales, Raquel; Romero, Irene; Fernandez-Caballero, Carlos; Escribano, M. Isabel; Merodio, Carmen; Sanchez-Ballesta, M. Teresa (Frontiers in Plant Science, 2016)
Table grapes (Vitis vinifera cv. Cardinal) are highly perishable and their quality deteriorates during postharvest storage at low temperature mainly because of sensitivity to fungal decay and senescence of rachis. The application of a 3-day CO2 treatment (20 kPa CO2 + 20 kPa O2 + 60 kPa N2) at 0ºC reduced total decay and retained fruit quality in early and late-harvested table grapes during postharvest storage. In order to study the transcriptional responsiveness of table grapes to low temperature and high CO2 levels in the first stage of storage and how the maturity stage affect these changes, we have performed a comparative large-scale transcriptional analysis using the custom-made GrapeGen GeneChip®. In the first stage of storage, low temperature led to a significantly intense change in grape skin transcriptome irrespective of fruit maturity, although there were different changes within each stage. In the case of CO2 treated samples, in comparison to fruit at time zero, only slight differences were observed. Functional enrichment analysis revealed that major modifications in the transcriptome profile of early- and late-harvested grapes stored at 0ºC are linked to biotic and abiotic stress-responsive terms. However, in both cases there is a specific reprogramming of the transcriptome during the first stage of storage at 0ºC in order to withstand the cold stress. Thus, genes involved in gluconeogenesis, photosynthesis, mRNA translation and lipid transport were up-regulated in the case of early-harvested grapes, and genes related to protein folding stability and intracellular membrane trafficking in late-harvested grapes. The beneficial effect of high CO2 treatment maintaining table grape quality seems to be an active process requiring the induction of several transcription factors and kinases in early-harvested grapes, and the activation of processes associated to the maintenance of energy in late-harvested grapes.